ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA KONVEKSI SITH APPAREL - Mun'im, Miftahul (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to explain about Tangible, Responsiveness and Assurance to customer satisfaction in Sith Apparel convection. This type of research is qualitative with a descriptive approach. Data collection techniques in this study using Observation, Interview and Documentation. The data analysis technique of this research uses data reduction, data presentation, drawing conclusions. To test the validity of this study, the researcher used the triangulation technique. Based on the results of this study, the Responsiveness and Assurance indicators have been running well. However, there are some of the Tangible indicators that still need to be improved. Examples such as buildings, there is no indoor temperature controller and the parking area is not wide enough. The results of the research can be input for Sith Apparel convection in order to provide the best quality service for consumers and Sith Apparel convection can develop in the future.